RIPK1 expression and inhibition in tauopathies: implications for neuroinflammation and neuroprotection - Silva-Llanes, Ignacio; Madruga, Enrique; Martínez, Ana; Lastres-Becker, Isabel (Frontiers in Neuroscience, 2025)
Tauopathies are a group of neurodegenerative diseases characterized by the alteration/aggregation of TAU protein. One of the main challenges of these diseases is that they have neither biomarkers nor pharmacological targets to stop the neurodegenerative process. Apart from the neurodegenerative process, tauopathies are also characterized by a chronic low-grade neuroinflammation process, where the receptor-interacting protein kinase 1 (RIPK1) protein plays an essential role. Our research aimed to explore the role of RIPK1 in various tauopathies. We examined mouse models of frontotemporal dementia (FTD), as well as brain tissue samples from patients with progressive supranuclear palsy (PSP), a primary form of 4R tauopathy, and Alzheimer’s disease (AD), which is considered a secondary tauopathy. Our findings show elevated levels of RIPK1 mRNA levels across various forms of tauopathies, in both mouse models and human tissue samples associated with primary and secondary TAU-related disorders. Furthermore, we investigated the potential of using a RIPK1 inhibitor, known as GSK2982772, in a mouse model as a novel treatment strategy for FTD. The data showed that GSK2982772 treatment effectively reduced the reactive astrocyte response triggered by TAUP301L overexpression. However, this RIPK1 inhibitor failed to protect against the neurodegeneration caused by elevated TAUP301L levels in the hippocampal region. These results suggest that although inhibiting RIPK1 activity may help reduce TAU-related astrogliosis in the brain, the complexity of the inflammatory pathways involved could explain the absence of neuroprotective effects against TAU-induced neurodegeneration.